The Fear and Allee-Effect on The Dynamics of A Food Chain Model Involving Additional Food to Predators - Shawka, Inaam Ibrahim; Majeed, Azhar Abbas (Iraqi Journal of Science, 2025)
In this paper, a food chain model with fear, Allee effect and linear harvesting in prey population with additional food and nonlinear harvesting in predator’s population have been advanced and studied. Furthermore, it is assumed that the predators are feed on prey using Crowley-Martin functional response. The existence, uniqueness and boundedness of the solution have been discussed. The conditions of local and global stability have been found. The aim of this study is to determine the fear, Allee and additional food effect on the stability of the proposed system, it has been shown that they have an important effect in controlling the stability of the system. Finally, numerical simulation carried out by using Mathematica to verify our analytical results.